Serratia sp. traits distinguish the lung microbiome of patients with tuberculosis and non-tuberculous mycobacterial lung diseases - Meriem Belheouane; Barbara Kalsdorf; Stefan Niemann; Karoline I. Gaede; Christoph Lange; Jan Heyckendorf; Matthias Merker (PLoS ONE, 2025)
Background Pathogenic mycobacteria, such as Mycobacterium tuberculosis complex (Mtbc), and non-tuberculous mycobacteria (NTMs) can cause severe chronic pulmonary infections. However, not all infected patients develop active disease, and it remains unclear whether key lung microbiome taxa play a role in the pathogenesis of tuberculosis (TB) and NTM lung diseases (LD). Here, we aim to further define the lung microbiome composition in TB, and NTM-LD prior to the initiation of therapy. Study design We employed 16S rRNA amplicon sequencing to characterize the baseline microbiome in bronchoalveolar lavage fluid (BALF) from patients diagnosed with TB (n = 23), NTM-LD (n = 19), or non-infectious inflammatory disease (n = 4). We applied depletion of human cells, removal of extracellular DNA, implementation of a decontamination strategy, and exploratory whole-metagenome sequencing (WMS) of selected specimens. Results Genera Serratia and unclassified Yersiniaceae dominated the lung microbiome of most patients with a mean relative abundance of >15% and >70%, respectively. However, at the sub-genus level, as determined by amplicon sequence variants (ASVs), TB-patients exhibited increased community diversity, and distinct signatures of ASV_7, ASV_21 abundances which resulted in a significant association with disease state. Exploratory WMS, and ASV similarity analyses suggested the presence of Serratia liquefaciens, Serratia grimesii, Serratia myotis and/or Serratia quinivorans in TB and NTM-LD patients. Conclusions The lung microbiome of TB-patients harbored a distinct, and heterogenous structure, with specific occurrences of certain Serratia traits. Some of these traits may play a role in understanding the microbial interactions in the lung microbiome of patients infected with Mtbc.